Development Of Motor Stories (Cermot) To Improve Fine Motor Skills Of Children Aged 4-6 Years At Nurul Hidayah Kindergarten, Purwakarta - Wahyuni, Mila; Priyanti, Nita (Kirana Publisher (KNPub), 2025)
This study aims to Development of Motor Stories (CERMOT) to Improve Fine Motor Skills Of Children Aged 4-6 Years at Nurul Hidayah Kingdegarten, Purwakarta and also to determine whether or not the media that has been developed is feasible. This study uses the type of Research and Development (R&D) research with the development model used is the ADDIE model. The design of the development model in this study goes through 7 stages, namely preliminary research, needs analysis, model design, expert and practitioner tests, model revision, product trials, and final model development. Data collection techniques used consist of observation, interviews and documentation. Data analysis includes analysis of the level of validity, analysis of product feasibility. The results of the study are: (1) The results of the assessment of the feasibility of Motor Stories (CERMOT) by each expert are the value of the Material Expert of 88% (Very Feasible), Media Expert of 89% (Very Feasible), the Child Development Expert gave 90% (Very Feasible) and Practitioner Expert of 91% (Very Feasible). (2) The fine motor skills of Nurul Hidayah Kindergarten students increased compared to before using the motor story media (CERMOT) as seen from the results of the Pre-Test and Post-Test, the average Pre-Test value was 54.9 and the Post-Test value was 88.2, which means there is a difference between learning before and after using the Motor Story media (CERMOT).